2009
DOI: 10.1088/1126-6708/2009/09/009
|View full text |Cite
|
Sign up to set email alerts
|

Holographic stress tensor for non-relativistic theories

Abstract: We discuss the calculation of the field theory stress tensor from the dual geometry for two recent proposals for gravity duals of non-relativistic conformal field theories. The first of these has a Schrödinger symmetry including Galilean boosts, while the second has just an anisotropic scale invariance (the Lifshitz case). For the Lifshitz case, we construct an appropriate action principle. We propose a definition of the non-relativistic stress tensor complex for the field theory as an appropriate variation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
356
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(365 citation statements)
references
References 43 publications
9
356
0
Order By: Relevance
“…This different scaling in fact means the notion of a boundary itself is altered; using the Penrose definition of a conformal boundary leads to a degenerate boundary metric. However, more careful treatments have shown that there is still a reasonable notion of a boundary as the location where metric components go to infinity, and holographic calculations can be performed using suitable prescriptions [5][6][7][8][9][10][11].…”
Section: Jhep01(2014)062mentioning
confidence: 99%
See 3 more Smart Citations
“…This different scaling in fact means the notion of a boundary itself is altered; using the Penrose definition of a conformal boundary leads to a degenerate boundary metric. However, more careful treatments have shown that there is still a reasonable notion of a boundary as the location where metric components go to infinity, and holographic calculations can be performed using suitable prescriptions [5][6][7][8][9][10][11].…”
Section: Jhep01(2014)062mentioning
confidence: 99%
“…We will consider an ansatz which allows for analysis of all these cases. Much recent progress has been made in creating a complete bulk/boundary dictionary for nonrelativistic systems [5,6,8,10]. In the well studied case of Lorentzian AdS/CFT, an important part of this dictionary is the correspondence between normalizable modes, which scale as r ∆ + near the boundary, and states in the Hilbert space of the dual field theory.…”
Section: Jhep01(2014)062mentioning
confidence: 99%
See 2 more Smart Citations
“…[12,13,14]. The holographic description of asymptotically Lifshitz spacetimes was studied in [15]. More recent investigations related to Lifshitz black holes can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%